Pengaruh Ustadz-Ustadz Muda Sebagai Penggiring Dakwah dan Hijrah Anak Muda - Eka Susanti; Muhammad Rizali Rahman (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The presence of young ustadz has become a major influence in the da'wah and hijrah movements of young people today and has become a significant phenomenon in recent years. They managed to influence and invite young people to hijrah and be able to carry out the obligations of Islamic da'wah together. This study aims to describe the influence of young ustadz as a driver of da'wah and hijrah among young people through da'wah communities that they form by adjusting the times and styles of today's youth. This research uses the library research method. The results showed that young ustadz and the current Islamic preaching and hijrah community have a strong influence in inspiring and directing young people to live piously and obey the rules of Allah Swt, but still follow the times. This proves that Islam is a religion following human nature and will always be suitable for every era.